Remarkable response to third-generation EGFR-TKI plus crizotinib in a patient with pulmonary adenocarcinoma harboring EGFR and ROS1 co-mutation: a case report - Wu, Zhiming; Zhang, Zelin; Zhang, Dongdong; Li, Zengyan (Frontiers in Oncology, 2024)
Background ： Driver oncogene mutations, such as c-ros oncogene 1 (ROS1) and epidermal growth factor receptor (EGFR) were previously believed to be mutually exclusive in non-small cell lung cancer (NSCLC).Only sporadic cases of ROS1 and EGFR co-mutations have been reported.Hence, appropriate treatment options for these patients are still controversial.Case presentation: A 48-year-old female patient presented at our hospital complaining of a persistent cough that had been ongoing for a month. A chest computed tomography showed a mass in the left lung along with hilar and mediastinal lymphadenopathy. Pathological analysis of bronchoscopic biopsy and lung mass puncture confirmed the presence of lung adenocarcinoma. The patient was diagnosed with stage IIIC left lung adenocarcinoma with a clinical stage of cT2N3M0. Next-generation sequencing analysis conducted at both puncture sites revealed an EFGR 19 deletion mutation combined with ROS1 rearrangement. The lung mass exhibited a higher mutation abundance. Treatment with a combination of third-generation EGFR tyrosine kinase inhibitors (TKIs) and crizotinib yielded satisfactory results. During the follow-up period, the mass significantly reduced and almost disappeared.The co-mutation of EGFR and ROS1 is a rare phenomenon.Nevertheless, the combination of EGFR-TKI and crizotinib treatment appears to hold promise in providing positive results for patients, with manageable side effects. This therapeutic approach has the potential to enhance patients' overall prognosis.